Alpha Defensin Lateral Flow Test for Diagnosis of Periprosthetic Joint Infection: Not a Screening but a Confirmatory Test. (2nd May 2018) - Renz, Nora; Yermak, Katsiaryna; Perka, Carsten; Trampuz, Andrej
Abstract : Background: Determination of alpha defensin in synovial fluid has shown promising results for diagnosing periprosthetic joint infection (PJI). The purposes of our study were to assess the performance of alpha defensin lateral flow (ADLF) test for the diagnosis of acute and chronic PJI using 3 classification systems and to compare its performance with the synovial fluid leukocyte count. Methods: Patients in whom aspiration of a prosthetic hip or knee joint was performed before revision arthroplasty were prospectively included. In addition to standard diagnostic tests, the ADLF test was performed in synovial fluid. Patients were classified as having PJI or aseptic failure according to the definition criteria of the Musculoskeletal Infection Society (MSIS), the Infectious Diseases Society of America (IDSA), and the proposed criteria of the European Bone and Joint Infection Society (EBJIS). The performance of the ADLF test and the leukocyte count was compared using the McNemar chi-square test. Results: Of 212 included patients, 151 (71%) had a knee prosthesis and 61 (29%) had a hip prosthesis. PJI was diagnosed in 45 patients (21%) using the MSIS criteria, in 55 patients (26%) using the IDSA criteria and in 79 patients (37%) using the proposed EBJIS criteria. The sensitivity of the ADLF test was 84% (95% confidence interval [CI], 71% to 94%) with the MSIS criteria, 67% (95% CI, 53% to 79%) with the IDSA criteria, and 54% (95% CI, 43% to 66%) with the proposed EBJIS criteria. The ADLF test showed high specificity using all classification criteria (96% to 99%) and represented the most specific preoperative test for PJI, especially in the early postoperative period (91%; 95% CI, 59% to 100%). Using the proposed EBJIS definition criteria, the sensitivity of the leukocyte count was significantly higher than that of the ADLF test (86% [95% CI, 76% to 93%] compared with 54% [95% CI, 43% to 66%]; p < 0.001), particularly in chronic PJI (81% compared with 44%, respectively; p < 0.001). Conclusions: The ADLF test was rapid and highly specific for diagnosing PJI (>95%). However, its sensitivity was limited (54% to 84%) and it should therefore not be used for screening, but rather as a confirmatory test for PJI. Level of Evidence: DiagnosticLevel I . See Instructions for Authors for a complete description of levels of evidence.